Implementasi Green Building dalam Mewujudkan Net Zero Healthy School - Vieraca Recaron Aldolyn; Yusvika Ratri Harmunisa (Universitas Medan Area, 2026)
School buildings play a strategic role in supporting the educational process while also contributing to environmental quality. Amid rising carbon emissions and worsening environmental conditions, the implementation of the green building concept has become a crucial solution in designing energy-efficient and environmentally friendly schools. This study examines the application of sustainable architectural principles, including energy efficiency, the use of renewable energy sources, improved indoor air quality, and user comfort. Case studies conducted at several elementary schools in DKI Jakarta demonstrate that optimizing natural ventilation, natural lighting, and the use of solar panels can significantly reduce energy consumption and carbon emissions. The findings affirm that the adoption of green building principles not only creates a healthy and comfortable physical environment but also fosters an educational ecosystem that supports the long-term goal of achieving net-zero carbon emissions.